Periodontal recession in patient from the Rodas Municipality. Cienfuegos, 2016-2017 - Beatriz Díaz Fabregat; Ana Laura Brito González; Nivia Gountán Quintana (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: The analysis of the health situation at present shows an increase in periodontal recession, disease which is a significant oral health problem. Objective: to characterize periodontal recession in patients from the Rodas municipality, Cienfuegos province. Methods: a descriptive study was developed in Rodas, Cienfuegos province, from October 2016 to 2017. Twenty two patients with the diagnosis of periodontal recession, according to the variables age, sex, educational level, risk factors for periodontal recession, dental group affected and degree of recession (according to the Miller classification). The information was obtained from the individual clinical records of dentistry and of periodontics. Results:  the age group 35 to 59 and female sex was the most affected. The most frequent risk factors were the presence of calculus or dento-bacterial plaque which is a sequel of chronic destructive periodontal disease and the lack of function of the implied teeth due missing teeth. The canine bicuspid dental group presented recession more frequently and class II prevailed. Conclusion: elements as educational level and the most important risk factors that affect this population are determinant to carry out actions against this disease from which other oral conditions may appear similarly pathological.